Brucella Infection Associated with Complete Atrioventricular Block - Meki Bilici; Fikri Demir; Murat Muhtar Yılmazer; Fatma Bozkurt; Volkan Tuzcu (Balkan Medical Journal, 2016)
Background: The clinical spectrum of Brucella infection is quite diverse and characterized by multi-system involvement. Patients present with myocarditis, endocarditis, or pericarditis. Infective endocarditis is the most common cardiovascular complication in patients with brucellosis. Although conduction abnormalities are seen in cases with endocarditis, they are reported very rarely in the setting of cardiac Brucella infection.